2017
DOI: 10.5423/ppj.ft.10.2016.0233
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Barley yellow dwarf virus Movement Protein Modulating Programmed Cell Death in Nicotiana benthamiana

Abstract: Barley yellow dwarf virus (BYDV) belongs to Luteovirus and is limited only at phloem related tissues. An open reading frame (ORF) 4 of BYDV codes for the movement protein (MP) of BYDV gating plasmodesmata (PD) to facilitate virus movement. Like other Luteoviruses, ORF 4 of BYDV is embedded in the ORF3 but expressed from the different reading frame in leaky scanning manner. Although MP is a very important protein for systemic infection of BYDV, there was a little information. In this study, MP was characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…The expression of P4 PAV and P4 PAS in N. benthamiana elicits a response by the plant that leads to cell death in the infiltrated tissues, and the degree of necrosis directly correlates with P4 titers. Similar observations were recently reported for BYDV P4 [ 59 ]. Different poleroviral P0 proteins (P0 PL , P0 CY , P0 SC and beet western yellows virus P0) have also been reported to trigger necrosis in infiltrated tissues [ 20 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…The expression of P4 PAV and P4 PAS in N. benthamiana elicits a response by the plant that leads to cell death in the infiltrated tissues, and the degree of necrosis directly correlates with P4 titers. Similar observations were recently reported for BYDV P4 [ 59 ]. Different poleroviral P0 proteins (P0 PL , P0 CY , P0 SC and beet western yellows virus P0) have also been reported to trigger necrosis in infiltrated tissues [ 20 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…demonstrated that the activation of anthocyanin biosynthesis in Arabidopsis can suppress the cell death caused by OY-W phytoplasma infection 60 . Coincidently the MP of a plant virus within the same family as BrYV, named Barley yellow dwarf virus , may trigger the programed cell death (PCD) on tobacco leaves in a dose-dependent manner 71 . Thus, the anthocyanin accumulated in BrYV-infected Arabidopsis may function as an anti-oxidant like it does in OY-W phytoplasma-infected Arabidopsis, whereas no sign of PCD was found on the transgenic Arabidopsis plants generated in this study, implying that there might be an integrative relationship among the anthocyanin concentration, the viral titter and PCD in plants.…”
Section: Discussionmentioning
confidence: 99%
“…These included tiny puncta associated with the nucleus, diffuse fluorescence within the nucleolus, and punctate spots (presumably PD) located along the cell wall. Localization of luteovirid P17 fluorescent protein fusions to PD and nuclei has been previously reported [ 21 , 22 , 45 , 46 ]. However, chloroplast localization was only observed when the first 79 to 99 residues of P17 were deleted [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, chloroplast localization was only observed when the first 79 to 99 residues of P17 were deleted [ 22 ]. Cytoplasmic aggregation of P17 fusion proteins has also been reported [ 45 ]. In our hands, expression of PLRV P17 fused to full-length enhanced cyan fluorescent protein (ECFP) at its C-terminus resulted in different subcellular localization patterns depending on the optical density (OD 600 ) of the A. tumefaciens culture used for infiltration ( Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%